STUDY ON MORPHOMETRIC AND MERISTIC OF Trichogaster trichopterus IN THE FLOOD AREAS OF THE TAPUNG RIVER AND FAPERIKA DAM - Eva Susanna; Windarti '; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
A study aims to understand the morphological and meristical characteristics, relative growth and condition factor of Trichogaster trichopterus has been conducted on Juni to Agustus 2013. Twenty five fishes (56-84 mm TL and 3,63-6,52 gr) from the Tapung River and 29 fishes (55-102 mm TL and 2,00-15,18 gr) from the FAPERIKA Dam were collected and measured. There were 13 meristical and 25 morphological characteristics have been studied. Meristical characteristics of the fins of the Tapung’s fish were as follows: D. VI-VII, P.9-14, A.IX-XII. 30-36, C.16-22 and those of the dam fish were as follow D.V-VII, P. 9-12, A. IX-XII. 30-36, C.16-21. The number of scales in the frontal area of the dorsal fin was 22-27, in the lateral line was 32-41, above the lateral line was 11-14, below the lateral line was 13-16, around the body was 42-62 and around the base of the tail was 24. There were 5 types of relative growth patterns of the morfological characteristic measured from the Tapung’s fish and that of the FAPERIKA Dam was 1 types. Length-weight relationship of Trichogaster trichopterus from both sampling sites were isometric.Key words: Trichogaster trichopterus, flood areas, Tapung River, morphological characteristic, meristical characteristic